Emersion of Distal Domains in Advanced Stages of Continental Rifting Explained by Asynchronous Crust and Mantle Necking. (21st August 2019) - Chenin, Pauline; Manatschal, Gianreto; Decarlis, Alessandro; Schmalholz, Stefan M.; Duretz, Thibault; Beltrando, Marco
Abstract: We propose an explanation to the enigmatic synrift erosional unconformities reported along the distal domain of several magma‐poor rifted margins. Using thermomechanical numerical modeling, we show that transient emersion of (future) distal domains following a phase of subsidence can be explained by asynchronous necking of first the upper mantle and subsequently the crust, without the need of prominent normal faulting caused by strain softening, mantle phase transitions, or magmatic processes. When the upper crust and upper mantle are mechanically decoupled by a weak lower crust and, in the absence of any prominent rheological heterogeneity, upper mantle, necking starts first because of the higher deviatoric stresses associated with its larger effective viscosity. Consequently, the ductile lower crustal material flows toward the necked mantle domain, delaying thinning of the overlying crust. Once the necked lithospheric mantle has locally lost most of its strength, the overdeepened Moho moves upward toward an isostatically compensated depth. This flexural rebound causes uplift and emersion of distal parts of the rift system that are composed of still relatively thick crust and triggers the necking of the overlying crust. Early necking of the upper mantle causes a transient heating event with temperatures up to 750 °C at the base of the crust in the (future) distal domain. The onset of this thermal event slightly predates emersion of the (future) distal domain. These results are consistent with field observations and thermochronological data from the fossil Alpine Tethys margins, as well as with seismic observations from several present‐day rifted margins. Key Points: Flexural rebound following early upper mantle necking can cause emersion of distal parts of rift systems Emersion of distal parts of rift systems is coeval with or postdates a regional thermal pulse at the base of the crust